Endoscopic stent placement with laparoscopic stent fixation in a patient with obstruction at a gastrojejunostomy anastomosis site - Kiwa Son; Koji Shindo; Kenoki Ouchida; Taiki Moriyama; Koji Tamura; Kinuko Nagayoshi; Yusuke Mizuuchi; Naoki Ikenaga; Kohei Nakata; Masafumi Nakamura (Surgical Case Reports)
Abstract Background Palliative endoscopic stent placement may be considered in patients with malignant gastrointestinal obstruction. Stent migration is a potential complication, particularly for those placed at a surgical anastomosis or across a stricture caused by extra-alimentary tract factors. We report a patient with left renal pelvis cancer and gastrojejunostomy obstruction who underwent endoscopic stent placement and laparoscopic stent fixation. Case presentation A 60-year-old male with peritoneal dissemination of a left renal pelvis cancer was admitted for treatment of upper gastrointestinal obstruction. A laparoscopic gastrojejunostomy had been previously performed for cancer invasion of the duodenum. Imaging showed gastroduodenal dilation and impaired passage of contrast medium through the efferent loop of the gastrojejunostomy. Gastrojejunostomy anastomosis site obstruction due to dissemination of left renal pelvis cancer was diagnosed. Conservative treatment failed and endoscopic stent placement with laparoscopic stent fixation was performed. After surgery, the patient was able to tolerate oral intake and he was discharged without complications. The patient gained weight and was able to resume chemotherapy, indicating the procedure was effective. Conclusions Endoscopic stent placement with laparoscopic stent fixation for malignant upper gastrointestinal obstruction appears effective in patients with a high risk of stent migration.